Reading an academic expository text – The ESL learner’s experience - Mohd Noor, Noorizah (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
Researches on approaches to learning have often described students as either deep or surface learners. In essence, the deep approach is associated with intrinsic motivation, a focus on understanding the meaning of the learning material and relating new ideas to previous knowledge. In contrast, the surface approach views a particular task in isolation, a focus on memorizing discrete facts and reproduces terms through rote learning. Although these studies have provided information on the qualitative differences of learning in various contexts, little research has been conducted to examine the students’ learning approaches within an ESL context. Accordingly, the primary purpose of this paper is to describe and compare six ESL learners’ approaches of two readings of an academic expository text. Three instruments were used to collect data: reading sessions, individual interviews and observations, whereby all sessions were videotaped, audio taped and transcribed verbatim. Findings of the study revealed that there were qualitative differences in the ESL approaches of reading an academic expository text and that different types of approaches were employed in the two readings of the text. To conclude, the paper will further discuss the implications of the findings and some pedagogical considerations for the teaching and learning of reading within an ESL context.